PERAN PEMUDA DALAM PEMBANGUNAN POLITIK HUKUM DI INDONESIA - Heri, Jon (Nurani, 2015)
Abstract: Youth is not just age, but also ideas, namelyProgressive , Radicals , militancy is strong, so he was able tobecome the motor and the locomotive of the changes that will becarried. The youth benchmark is how much fighting spirit toward off weakness and laziness. Morale and commitment tocontinue to work that must be nurtured by a youth claiming toIndonesia, as a form of offering the best to build the nation andthe country.ملخص: الشباب لیس سن فقط، ولكن أیضا الأفكار، وھي التقدمي، والجذور، التشددقوي، حتى انھ كان قادرا على أن یصبح المحرك و قاطرة التغییرات التي سیتم تنفیذھا.لا تقاس على روح الشباب من قبل العضلات قوي للبشرة البكر و البكر. ولكن،والشباب المؤشر الروح ھو مقدار الروح القتالیة لدرء الضعف و الكسل. مدى قوةالالتزام صیانة و تحسین العمل. الروح المعنویة و الالتزام بمواصلة العمل التي یجبرعایتھا من قبل شاب یدعي اندونیسیا، كشكل من أشكال تقدیم الأفضل ل بناء الأمةوالدولة.Kata Kunci: Pemuda, Pembangunan Politik